References to Prophecy in Neo‐Assyrian Sources - Postgate, J. N. (Journal of Semitic studies, 2002)
References to Prophecy in Neo‐Assyrian Sources MarttiNissinen (State Archives of Assyria Studies 7). The Neo‐Assyrian Text Corpus Project, University of HelsinkiHelsinki 1998x + 194Paperback$35.00 951‐45‐8079‐6 , 1Trinity College, Cambridge